(untitled) (Research, Society and Development, 2024)
Objectives: to highlight the challenges that these young people face in promoting autonomy for self-care with limited accessibility to information, old medication application techniques, low adherence to treatment and obstacles in the family environment. METHODS: an integrative literature review was carried out during the period from July 2022 to February 2024, selecting a sample of 120 articles and after all selection, 6 scientific articles were highlighted for the production of the study. Discussion And Results: Furthermore, it was evident that in order to build patient autonomy in relation to their treatment, resulting in self-care, it is necessary for young people to be able to achieve the three pillars of self-care: cognitive autonomy; behavioral autonomy; and emotional autonomy. In view of the above, several factors end up harming the individual’s personal development, such as a family that is too protective or shows poor adaptation to the patient’s new reality. Access to information about the disease restricted to public health environments is also an important factor to be mentioned, the use of technologies to disseminate knowledge to this public in question is a reality that must be addressed.